The 500th Lung Transplantation at the Faculdade de Medicina da Universidade de São Paulo: Reflecting on Our Journey and Looking Ahead - dos Reis, Flavio Pola; Pêgo-Fernandes, Paulo Manuel (São Paulo Medical Journal, 2023)
Lung transplantation is a widely accepted therapeutic option for the treatment of some advanced lung diseases. With current medical advances and new technologies, discussions on terminal patients and the possibility administering of a treatment option, whose objective is to increase survival or at least the quality of life of patients, are gaining more attention.